An Empirical Study of Dispute Resolution Clauses in International Supply Contracts - Coyle, John F.; Drahozal, Christopher R. (Vanderbilt Journal of Transnational Law, 2018)
International transactions present unique legal risks. When a contract touches several different nations, a party may not know where it will be called upon to defend a lawsuit or, alternatively, which nation’s law will be applied to resolve that dispute. To mitigate these risks, parties will often write dispute resolution provisions into their contracts. Arbitration clauses and forum selection clauses help to reduce uncertainty relating to the forum. Choice-of-law clauses help to reduce uncertainty as to the governing law. Over the past few decades, such provisions have become commonplace in international contracting. And yet there exist vanishingly few empirical studies exploring the use of these provisions in international commercial agreements.

Institutional and Contextual Factors Effects on Entrepreneurship in Cameroon: The Case of the Transport Sector - Okah-Efogo, Françoise; Okah-Atenga, Crescence Marie-France (Entrepreneurship in Africa, 2017)
In Africa, whatever the considered age group, there are more entrepreneurs in the early stages of entrepreneurship than anywhere else in the world (Global Entrepreneurship Monitor (GEM) Report 2014). According to the gem survey (2014), 55.57 per cent of the population between 18–64 years expresses entrepreneurial intentions in Cameroon. Similarly, 37.4 per cent of the same age population is in the early course of their business activity. Between 2014 and 2015, total entrepreneurial activity has decreased in Cameroon (from 37.4 per cent to 25.4 per cent of all adults). Nonetheless, 61.1 per cent of the respondents think that entrepreneurship

Remedies for passengers for flight delays caused by force majeure - Ko, Li-Juan (McGill University, 2016)
This thesis intends to justify the necessity to propose an alternative remedy mechanism to current air carriers' obligations in offering complimentary services to passengers in force majeure delays. This mechanism mitigates disputes arising from passengers' dissatisfaction with air carriers' services. The proposal is the result of extensive research arising from a fundamental question: Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure? The source of information for this thesis stems from a combination of the analysis of case law and statutes on one hand, and experience drawn from professional practice and cultural context on the other. This thesis discusses the intersection of international conventions, national legislation, and the practice and expectations of air carriers and their passengers. The thesis specifically examines and highlights the inadequacies of relying on existing international conventions to provide a harmonized solution for flight delay claims. In terms of national remedy mechanisms, research and analysis have been focused on the advanced aviation markets in the West, such as the US and the EU, and on the emerging markets in the East, such as Mainland China and Taiwan. The research and analyses reveal how national laws, which are deeply influenced by socio-economic, political and cultural factors, trigger distinct conflicts of interest between air carriers and passengers. During the course of reviewing the legal jigsaw and uncertainties in current legal practice, the findings revealed more issues. In brief, making more laws cannot guarantee an effective solution for flight delay claims, especially in different jurisdictions. Accordingly, the findings support that a novel solution, free from the uncertainties and complexities in the current legal framework, is needed to resolve passengers' claims or expectations resulting from force majeure delays. Essentially, this novel solution is to form an alternative remedy mechanism that includes a fund and codes of conduct. The fund will implement a risk-sharing function among stakeholders that will include passengers, air carriers and airport managing entities. To mitigate disputes, the proposed codes of conduct will include guidelines to operate the fund with the aim of mutual respect between passengers and air carriers. In so doing, the remedy mechanism will provide equitable answers to the question: "Who should be responsible for damages and/or inconvenience resulting from flight delays caused by force majeure?"
Keywords: Air carriers' obligation; Alternative remedy; Flight delay; Force majeure; Remedies

A level playing field for "open skies": the need for consistent and harmonized regulation of Aviation - Fitzgerald, P. Paul (McGill University, 2015)
Various initiatives by regulators in different jurisdictions over the past two decades have completely reshaped the airline industry in ways that were unimaginable in 1992. From an industry dominated by Pan Am and Trans World Airlines (TWA), and newly privatized airlines such as British Airways, today's industry is dominated by government-owned intercontinental airlines based in the Middle East and carrying passengers the majority of whom are ultimately destined for States other than the States where the airlines are based. Insufficient thought has been given to whether this evolution is desirable, whether it involves profound competitive distortions or whether it is in the public interest that the majority of Australians visiting Europe are carried by an airline based in neither jurisdiction or that a similar claim might be made with respect to traffic between South Asia and the Americas. This thesis examines the events that have reshaped the international aviation industry over the two decades between 1992 and 2012. It will critically analyze the major developments and the regulatory responses and highlight some of the incompatible and disjointed regulations that are in effect at either end of international routes. It ultimately proposes that Australia, Canada, the European Union (EU), New Zealand and the United States (US) form a small international organization, to be known as the Open Skies International Aviation Block (OSIAB). OSIAB would be based on expanding the membership of the US-EU Joint Committee foreseen in the 2007 US-EU Open Skies Agreement and expanding its scope to cover every aspect of the regulation of international commercial aviation. This thesis argues such a forum is necessary to ensure that regulations in different countries are aligned so that competitive distortions potentially caused by regulatory disharmony are minimized, thus allowing the international airline industry to compete on the level international playing field that so many international agreements have promised to create.
Keywords: Aviation; Aviation regulation; Transport aérien

The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (34th Annual Southern African Transport Conference 6-9 July 2015, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Keywords: Southern African Transport Conference; Transportation